Behind the Screen Where Today's Bully Plays: Perceptions of College Students on Cyberbullying - Paullet, Karen (2014)
This exploratory study of 168 undergraduate students examined the perceptions of college students about cyberbullying. The study focused on students’ knowledge of the topic, opinions about cyberbullying, and personal experiences they may have had as either a victim or a witness of cyberbullying. Reporting of cyberbullying incidents was also explored, and participants were asked to indicate what can or should be done to prevent cyberbullying